2012
DOI: 10.1002/wsb.110
|View full text |Cite
|
Sign up to set email alerts
|

Utility of vocal formant spacing for monitoring sandhill crane subspecies

Abstract: Three migratory subspecies of sandhill crane (Grus canadensis) occur in North America: greater (G. c. tabida), Canadian (G. c. rowani), and lesser (G. c. canadensis). These subspecies vary clinally in size from the large tabida to the small canadensis. All 3 subspecies co‐occur during the nonbreeding season, but field identification is challenging and census efforts typically do not even attempt to distinguish them. We developed a novel method to determine the subspecies composition of nonbreeding sandhill cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Boeckle & Bugnyar () showed that ravens ( Corvus corax ) responded to calls of previously familiar and non‐affiliated individual by lowering the formant spacing and increasing the chaotic parts of the vocalisation in comparison with calls of an affiliated one, potentially exaggerating the perceived impression of body size. Moreover, formants can, at least in theory, provide acoustic cues to individuality and body size within the same bird's species, as previously demonstrated in mammals (Suthers ; Fitch ; Jones & Witt ).…”
Section: Introductionmentioning
confidence: 66%
“…Boeckle & Bugnyar () showed that ravens ( Corvus corax ) responded to calls of previously familiar and non‐affiliated individual by lowering the formant spacing and increasing the chaotic parts of the vocalisation in comparison with calls of an affiliated one, potentially exaggerating the perceived impression of body size. Moreover, formants can, at least in theory, provide acoustic cues to individuality and body size within the same bird's species, as previously demonstrated in mammals (Suthers ; Fitch ; Jones & Witt ).…”
Section: Introductionmentioning
confidence: 66%